Food and Nutrition knowledge Attitudes and Practices (KAP) of public primary school children in the communes of Cotonou, Abomey-Calavi and Sèmè-Kpodji - Koukou, Elie; Bodjrenou, Fifali Sam Ulrich; Yanausse Bello, Faick Moctar; Amoussa Hounkpatin, Waliou; Termote, Celine (2024)
This study targeted public primary school children in the third, fourth and fifth grades in the communes of Cotonou, Abomey-Calavi and Sèmè-Kpodji. The purpose is to assess their food and nutrition knowledge, attitudes and practices.